Effect of residual stress on the stress corrosion cracking in boiling magnesium chloride solution of austenite stainless steel. Issue 11 (14th June 2018) - Wu, Huanchun; Li, Chengtao; Fang, Kewei; Zhang, Wenqian; Xue, Fei; Zhang, Guodong; Wang, Xuelin
Abstract : The effect of residual stress on the stress corrosion cracking (SCC) behaviors of Z3CN20.09M, 304L and 316L austenitic stainless steels (SSs) in boiling magnesium chloride solution were investigated by X‐ray diffraction, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The residual stress of surface and the hardness tested on the cross section of specimens induced by milling operation was decreased with increasing annealing temperature. The crack densities were also decreased with increasing annealing temperature of the specimens, and the SCC did not occur after annealed at 600 °C for 3 h except 316L SS when tested in boiling magnesium chloride solution. Crack initiation mechanism related to the damaged effect on grain boundary during milling operation was analyzed. The double loop electrochemical potentiokinetic reactivation (DL‐EPR) tests indicated that the effect of annealing treatment up to 600 °C on intergranular (IG) corrosion susceptibility of 304L and 316L SSs was minor, while it remarkably increased of the Z3CN20.09M SS. Abstract : The crack densities decreased with increasing the annealing temperature of the milled Z3CN20.09M, 304L and 316L stainless steels (SS). The crack initiation was not obvious decreased of specimens after annealed at 300 °C, while there was no crack initiated for specimens after annealed at 600 °C except 316L SS.